From NAFTA to surveillance capitalism: USMCA's digital order - Burcu Kilic (Centre for International Governance Innovation (CIGI), 2025)
In 1994, the North American Free Trade Agreement laid the groundwork for today's neo-liberal global trade order. Three years later, the US government's Framework for Global Electronic Commerce enshrined minimal government intervention and industry self-regulation for the tech industry, principles that have since defined US digital trade policy, culminating in the digital chapter of the United States-Mexico-Canada Agreement (USMCA). Digital technologies, central to commerce, governance and daily life, also pose numerous challenges. Competition authorities, privacy regulators and worker advocates now question the surveillance capitalist business model, yet trade rules continue to reinforce and legitimize it. Technology policy is a key focus of the ongoing negotiations over tariffs reinstated when US President Donald Trump took office in January 2025, which has provided an opening for tech companies to cast tariffs as market-correcting mechanisms. The formal review of the USMCA scheduled for July 1, 2026, represents a critical inflection point. This paper traces US digital trade policy from the Clinton-era vision of self-tech regulation to today's far-reaching digital trade framework. It reveals how current digital trade rules clash with contemporary economic and social priorities, as well as industrial policies, and warns negotiators that if North American trade is to deliver shared prosperity and technological development and protect worker well-being, digital trade should shift from embracing surveillance capitalism to restoring democratic accountability.
Keywords: 330